2010
DOI: 10.1007/s10545-009-9013-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of keratan sulfate level in mucopolysaccharidosis type IVA by liquid chromatography–tandem mass spectrometry

Abstract: Mucopolysaccharidosis type IVA (MPS IVA, Morquio A disease), a progressive lysosomal storage disease, causes skeletal chondrodysplasia through excessive storage of keratan sulfate (KS). KS is synthesized mainly in cartilage and released to the circulation. The excess storage of KS disrupts cartilage, consequently releasing more KS into circulation, which is a critical biomarker for MPS IVA. Thus, assessment of KS level provides a potential screening strategy and determines clinical course and efficacy of thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
103
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 59 publications
(114 citation statements)
references
References 20 publications
10
103
0
1
Order By: Relevance
“…4GlcNAc(6S). Our previous results showed that the proportion of di-sulfated KS in total KS in the patients with MPS IVA is higher than that in the control subjects (Tomatsu et al 2010c); but the low sensitivity and specificity of the assay to detect di-sulfated KS limited further studies. Improvement of the assay method to separate di-sulfated KS and mono-sulfated KS was needed to distinguish MPS IVA, control subjects, and other types of MPS precisely.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…4GlcNAc(6S). Our previous results showed that the proportion of di-sulfated KS in total KS in the patients with MPS IVA is higher than that in the control subjects (Tomatsu et al 2010c); but the low sensitivity and specificity of the assay to detect di-sulfated KS limited further studies. Improvement of the assay method to separate di-sulfated KS and mono-sulfated KS was needed to distinguish MPS IVA, control subjects, and other types of MPS precisely.…”
Section: Introductionmentioning
confidence: 89%
“…Similar methods have been validated in another laboratory (Martell et al 2011). KS levels in blood and urine in patients with MPS IVA are associated with age and clinical severity (Tomatsu et al 2010c) and are decreased with enzyme replacement therapy (ERT) on mouse model and bone marrow transplantation (BMT) in a patient with MPS IVA Chinen et al 2014). Thus, KS levels in the blood and/or urine should be a suitable biomarker for early diagnosis, screening, clinical severity, and therapeutic efficacy in MPS IVA (Tomatsu et al , 2010c(Tomatsu et al , 2013a.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations